Ensino de Ciências e formação de professores: diagnóstico, análise e proposta - Azevedo , Rosa Oliveira Marins (2008)
Research in the educational scope, specifically on teacher's formation, for effect of knowledge of how the teachers of the initial years of Basic Studies works with scientific concepts in Science Studies, when they use the new technologies. The adopted theoretical perspective pointed out the trajectory of Science Studies and its importance for students of the initial years of Basic Studies, indicating beddings to the quarrel of the formative necessities of the teacher of related education and school level. These necessities had lead the quarrels on the process of teach-learning of the scientific concepts, as well as the possibility of use of the new technologies, particularly the computer and the internet, as pedagogical resource to work such concepts. How much to the metodological perspective, on a qualitative research, legitimated research was constructed through strategies, as the comment and the interview. The State and Municipal Department of Education had been contacted and as well as three schools, for the collection data. From this, the research had been centered in a public school detainer of a large experience in Science Studies, making use of the new technologies. The collected data had been analyzed on the basis of the empiricist-interpretative analysis. The gotten results had shown that Science Studies if keeps centered in the transmission the students of the elaborated scientific knowledge already, from pedagogical practical one strong influenced by the memorization. Such this, beyond if constituting in impediments for the learning of the students, still points the limits out of the practical professor and its formation to teach Sciences. From this point, it was elaborated a pedagogical project of Specialization in Education of Sciences and New Technologies, as contribution for the formative process of professors of the initial years of Basic Studies and, consequently, for Science Studies.